The quark-mass dependence of the potential energy between static colour sources in the QCD vacuum with light and strange quarks - John Bulava; Francesco Knechtli; Vanessa Koch; Colin Morningstar; Michael Peardon (Physics Letters B, 2024)
The low-lying energy spectrum of the static-colour-source-anti-source system in a vacuum containing light and strange quarks is computed using lattice QCD for a range of different light quark masses. The resulting levels are described using a simple model Hamiltonian and the parameters in this model are extrapolated to the physical light-quark masses. In this framework, the QCD string tension is found to be σ=445(3)stat(6)sys MeV.